Aggressive Antisocial Behaviors Are Related to Character Maturity in Young Swedish Violent Offenders Independent of ADHD - Nilsson, Thomas; Falk, Örjan; Billstedt, Eva; Kerekes, Nóra; Anckarsäter, Henrik; Wallinius, Märta; Hofvander, Björn (Frontiers in Psychiatry, 2016)
Background: Antisocial personality and psychopathic traits have constantly been found to accompany criminal and aggressive behaviors, but little attention has been given to aspects of character maturity and its relation to such behaviors. The present study investigated 1) whether level of character maturity (low, medium, and high) is associated with amount of aggressive antisocial behaviors and psychopathic traits in young men imprisoned for violent criminality, and 2) whether such an association is independent of coexisting attention deficit hyperactivity disorder (ADHD). Methods: Swedish males (N=270, aged 18-25) sentenced to prison for violent and/or sexual criminality in the western region of the Swedish Prison and Probation Service underwent a thorough clinical examination during their incarceration. Data on character maturity as measured by the character dimensions Self-Directedness and Cooperativeness of the Temperament and Character Inventory were available for n=148 subjects, and used to divide these offenders into three groups with low, medium, and high character maturity. These groups were then compared for variables reflecting criminal history, a DSM-IV diagnosis of ADHD, Conduct disorder (CD) and substance use disorders (SUD), aggressive behaviors, and psychopathic traits. Results: Character maturity was consistently associated with less aggressive antisocial behaviors and psychopathic personality traits; the group with the highest character maturity showed; i) a later age at onset of criminality, ii) a smaller number of prior violent criminal acts, iii) lower prevalences of ADHD, CD, and SUD, iv) less self-rated and expert-rated aggressive behaviors, and v) less psychopathic traits. The association between character maturity and aggressive behaviors/psychopathic personality traits remained even when ADHD was controlled for. The only exception was sexual criminality, where the group with the highest character maturity contained the largest amount of sexual offenders. Conclusion: Higher character maturity appeared to be a protective factor among young male violent offenders, associated with less aggressive antisocial behaviors, suggesting that character maturity is a promising target for treatment interventions for this group of individuals.